2002
DOI: 10.1177/15648265020233s148
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Evaluation of Underutilized Cereals and Buckwheat

Abstract: We evaluated the nutritional factors of underutilized cereals (spelt, emmer, einkorn, millet, foxtail millet, semiperennial rye, naked oat, and naked barley) and buckwheat. The basic food components as well as minor nutrients were determined. The analyses included dry matter, ash, protein, dietary fiber, fat, fatty acids, amino acids, minerals, and lipophilic and hydrophilic vitamins. Rutin was also determined in buckwheat. We hope to offer new recipes for the healthy food production and for special dietary us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
5
16
1
Order By: Relevance
“…As an example, Ragaee et al 37 reported lower RS values (2 g kg −1 DW) in hard wheat, but the determinations were carried out on refined flours. Several studies have shown that whole grains contain higher concentrations of dietary fibre compared with wheat flours and would enhance dietary fibre intake 30, 38, 39…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Ragaee et al 37 reported lower RS values (2 g kg −1 DW) in hard wheat, but the determinations were carried out on refined flours. Several studies have shown that whole grains contain higher concentrations of dietary fibre compared with wheat flours and would enhance dietary fibre intake 30, 38, 39…”
Section: Resultsmentioning
confidence: 99%
“…In general, the total dietary fibre content of T. monococcum is low (Table ). Values inferior to 100 g kg −1 DM are reported by Abdel Aal et al , Grausgruber et al and Løje et al ; Gebruers et al state a mean value of 110 g kg −1 DM and a variation from 93 to 128 g kg −1 DM, while Gabrovská et al describe a 104 g kg −1 DM content. The total dietary fibre of other hulled wheats is similar (emmer, 98 g kg −1 DM; spelt, 120 g kg −1 DM), but that of free‐threshing wheats is higher, as reported by Gebruers et al (durum wheat, 134 g kg −1 DM; bread wheat, 147–152 g kg −1 DM) and Andersson et al (bread wheat, 134 g kg −1 DM).…”
Section: Carbohydratesmentioning
confidence: 91%
“…From a nutritional perspective, protein quality depends on amino acid content, proportion of essential amino acids, susceptibility to hydrolysis during digestion and rate of physiological utilization after absorption; food processing and interaction with other components of the diet modify their availability. Wheat storage proteins are low in some amino acids essential to the human diet, and T. monococcum is no exception, as its seed proteins are low in lysine and high in glutamic acid and proline . In general, the amino acid composition of einkorn kernels is thus very similar to that of polyploid wheats (Table ).…”
Section: Proteinsmentioning
confidence: 99%
“…Buckwheat has become more popular in many countries as a new healthy foodstuff (Fujimura, Minami, Watanabe, & Tadera, 2003;Gabrovska et al, 2002;Kreft, Strukelj, Gaberscik, & Kreft, 2002;Rapala, Ostrowska, Bednarczyk, Dulinski, & Kozik, 2003), but the occurrence of buckwheat allergy is also increasing in Asia and Europe (Kim et al, 2003;Nakamura & Yamaguchi, 1974;Wieslander et al, 2000), so authors have taken it up as the focus of this study. Many cases of buckwheat allergic subjects have been reported, and buckwheat might cause occupational asthma in noodle makers, bakers and packing workers (Davidson, Passero, & Settipan, 1992;De Maat-Bleeker & Stapel, 1998;Gö the, Wieslander, Ancker, & Forsbeck, 1983;Nakamura & Yamaguchi, 1974;Park & Nahm, 1996;Schumacher, Schmid, & Wü thrich, 1993;Takahashi, Ichikawa, Aihara, & Yokota, 1998;Wü thrich & Trojan, 1995).…”
Section: Detection Of Allergenic Proteins By Ige-immunoblottingmentioning
confidence: 91%